Data Flow Based Integration Testing - Vilela, Plínio R. S.; Maldonado, José C.; Jino, Mario (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1999)
An approach to extend Structural Unit Testing Criteria to the Integration Testing is presented. The approach is based on the concept of Potential Uses, which basically states that a data flow association exists between a definition of a variable and every point reachable from that definition through a definition-clear subpath, even without an explicit usage of the variable - it is called a potential data flow association. A practical procedure to implement the approach, based on testing information generated during unit testing, is also presented.